Pengaruh Kepercayaan, Brand Image dan Cashback Terhadap Keputusan Pembelian Konsumen Melalui Minat Beli Adidas pada Market Place Shopee - Alfatika, Fienska Chufina; Pakarti, Piji; Adhi Purusa, Nanda; Eric S.W, Mochammad (Jurnal Pendidikan Indonesia, 2024)
The aim of this analysis is to test and evaluate the effect of trust, brand image, and cashback on consumer buying interest in adidas in the shopee market place. To test and assess the effect of trust, brand image, cashback, and purchase intention on adidas consumer purchasing decisions in the shopee market place. The population studied was all adidas consumers in the shopee market place in Semarang City. This study used purposive sampling technique with 190 respondents. SEM PLS is the data analysis tool used. Based on empirical facts and the SEM PLS research model, it is found that trust has a positive and insignificant impact on the purchase intention of Adidas customers on the Shopee e-commerce website. Brand image has a positive and significant effect on buying interest in adidas consumers in Shopee e-commerce. Cashback has a positive and significant effect on buying interest in adidas consumers in Shopee e-commerce. Trust has a positive and insignificant effect on purchasing decisions for adidas consumers in Shopee e-commerce. Brand image has a positive and significant effect on purchasing decisions for adidas consumers in Shopee e-commerce. Cashback has a positive and significant effect on purchasing decisions for adidas consumers in Shopee e-commerce. Purchase interest has a positive and insignificant effect on purchasing decisions for adidas consumers in Shopee e-commerce. Purchase intention cannot mediate the influence of trust on purchasing decisions for adidas consumers in Shopee e-commerce through purchase intention. Purchase intention cannot mediate the influence of brand image on purchasing decisions for adidas consumers in Shopee e-commerce through purchase intention. Purchase intention cannot mediate the effect of cashback on purchasing decisions for adidas consumers in Shopee e-commerce through purchase intention